STRUCTURE OF SMALL-SCREET CONCRETE AND ITS INFLUENCE ON STRENGTH AND DEFORMATIVITY - Z. J. Pasieva; Sh. M. Davlyatov (Web of Journals Publishing, 2025)
The structure of concrete has a great influence on the strength and deformability of concrete. To clarify this issue, let's consider the scheme of the physicochemical process of concrete formation. When a mixture of aggregates and cement is mixed with water, a chemical reaction of cement minerals combining with water begins, resulting in the formation of a gel - a gelatinous porous mass with suspended cement particles and insignificant compounds in the form of crystals that have not yet entered into a chemical reaction. During the mixing process of the concrete mixture, the gel envelops individual aggregate grains, gradually solidifies, and the crystals merge over time into crystalline adherents. The hardening gel transforms into a cement stone that binds the grains of large and small aggregates into a monolithic solid concrete.
Keywords: Concrete structure, concrete essence, strength, deformability, process duration